2016
DOI: 10.1016/j.mad.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of APOE in human longevity revealed by high-throughput sequencing

Abstract: Apolipoprotein E (APOE) gene has been the most replicated longevity-associated gene in humans. Two common APOE alleles are either significantly depleted (ε4 allele) or enriched (ε2 allele) in long-lived individuals as compared to controls. We performed high-throughput sequencing analysis of exons and 2 kb proximal promoter of APOE in 450 centenarians and 500 controls of Ashkenazi Jewish decent. We found two common regulatory variants, rs405509 (p=0.006) and rs769449 (p=0.036), that were significantly depleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
0
20
2
Order By: Relevance
“…In particular, the ε2 allele is enriched in centenarians, compared with ε4 [37]. In the present study, the ε4 allele was not detected in any of the cases.…”
Section: Discussioncontrasting
confidence: 51%
“…In particular, the ε2 allele is enriched in centenarians, compared with ε4 [37]. In the present study, the ε4 allele was not detected in any of the cases.…”
Section: Discussioncontrasting
confidence: 51%
“…A recent study by Ryu et al (2016) of 450 centenarians revealed that APOE ε2 is associated with longevity and that the individuals in this cohort were significantly less likely ( p = 0.005) to carry the ε4 allele, with a frequency of 9.6 and 15.7 % in centenarians versus controls, respectively. This association has been observed in other cohorts (Louhija et al 1994; Schachter et al 1994; Mayila et al 2005) and may be due to a reduced risk of both cardiovascular disease and AD (Eichner et al 2002).…”
Section: Role Of Apoe In Admentioning
confidence: 66%
“…The data show a negative association with APOE-e4 allele suggesting that it has to be considered ''frailty'' rather than a true longevity allele 166,167 . On the contrary an enrichment of APOE-e2 allele was observed in long-lived individuals 165,168,169 and this suggests a protective role of this allele supported by a positive association between APOE-e2 and healthy cognitive status 169,170 .…”
Section: Apolipoproteins and Apoe/tomm40mentioning
confidence: 82%
“…These genetic variants likely influence lipoprotein profile, cardiovascular health and insulin sensitivity. Among all these genes the most replicated is the region of APOE/TOMM40 8,38,[122][123][124][125][126][127] , that is considered the "master" longevity gene 165 . The data show a negative association with APOE-e4 allele suggesting that it has to be considered ''frailty'' rather than a true longevity allele 166,167 .…”
Section: Apolipoproteins and Apoe/tomm40mentioning
confidence: 99%